Analisis Pengaruh Faktor Ekonomi Makro terhadap Nilai Ekspor Perikanan di Indonesia Tahun 2016-2022 - Abhirama Abraham Chaharto Putra; R.A. Norromadani Yuniati; Medi Prihandono (Proceeding Maritime Business Management Conference, 2024)
The contribution of the fisheries economy in Indonesia was very minimal to the national economy and does not align with the increase of fisheries exporst in Indonesia. This research aimed to analyze the influences of the gross regional domestic product (GRDP), and the value of fisheries production to the value of fisheries export in Indonesia in 2016-2022 also moderated by foreign direct investment (FDI) in the fisheries sector. This research was causal quantitative research using secondary data from the Ministry of Fishery and Ocean, Ministry of Trade, and Badan Pusat Statistik. The result of the study showed that partially, the variables of gross regional domestic product (GRDP) and fisheries production value have a positive effect on the value of fisheries exports, and foreign investment has a negative effect on the value of fisheries exports,. Foreign investment can negatively moderate the relationship between the value of fisheries production and the value of fisheries exports, but foreign investment is not able to moderate the relationship between GRDP to the value of fisheries exports. Policy, program, and action that focus on producer and production had to be a priority.